The Asymptotic Synchronization Analysis for Two Kinds of Complex Dynamical Networks - Ze Tang; Jianwen Feng (Advances in Mathematical Physics)
We consider a class of complex networks with both delayed and nondelayed coupling. In particular, we consider the situation for both time delay-independent and time delay-dependent complex dynamical networks and obtain sufficient conditions for their asymptotic synchronization by using the Lyapunov-Krasovskii stability theorem and the linear matrix inequality (LMI). We also present some simulation results to support the validity of the theories.